Trade-offs between health and absenteeism in welfare states: Striking the balance - Simen Markussen (University of Oslo, Department of Economics, 2007)
Workers'absenteeism due to illness represents a major concern in several countries. Absenteeism are however not very well understood in economics. This paper presents a model where absenteeism is understood in relation to health. Its main predictions are (i) intermediate welfare state generosity lead to the lowest absence rates as (ii) generous regimes results in excess long-term absenteeism and (iii) strict regimes lead to excess short-term absenteeism. (iv) Maximizing health is not the same as minimizing absenteeism. Finally, these predictions are supported by aggre- gate data for 12 OECD countries.
Keywords: C61; H53; H55; I31; J08; 330; Absenteeism; Health; Dynamic programming; Welfare state policies; Fehlzeit; Gesundheit; Sozialpolitik; Dynamische Optimierung; OECD-Staaten